Contextualizing the preaching of the Gospels through culture in the Dayak Keninjal tribe of West Kalimantan - Sirait, Junio Richson; Desi, Desi; Marsalina, Tania; Nortania, Nortania (KAMASEAN: Jurnal Teologi Kristen, 2025)
The aims of this paper are to analyze the Betangkant Children’s culture of the Dayak Keninjal tribe in an effort to contextualize God’s love. The study of the meaning and cultural aspects of raising children to apply the Gospels, or good news, in the context of the life of the Dayak Keninjal community. This research uses a literature review. The results of this study are as follows: Through the Betangkant Children’s culture of the Dayak Keninjal tribe, the village of Madyaraya will provide a meaningful context and an entry point for Dayak Keninjal to encounter Jesus Christ as Lord and Savior within the Keninjal tribe, thereby representing the relationship between the Father and the believers. Trusting children can make it easier to communicate God’s relationship with His people, like the relationship between a father and a child who has been raised in a culture of tension. The affirmation of the relationship between the Father and His children has been manifested in the love of God the Father through the sacrifice of the Lord Jesus Christ, which redeems and elevates believers into His beloved children.